Numerical simulations of 2-D steady and unsteady breaking waves. (15th September 2015) - Lupieri, Guido; Contento, Giorgio
Abstract: In this work we analyze by means of numerical simulations the features of breaking of two dimensional free surface waves induced by a body or a sloping bottom. The sample cases selected for the simulations characterize different aspects of wave breaking, thus they are supposed to represent rather widely a problem of large interest for ship hydrodynamics and ocean engineering applications. The simulations considered are: wave breaking induced by a fully submerged hydrofoil towed in calm water at constant speed; shallow water waves breaking on a sloping beach in spilling and plunging mode; regular intermediate depth waves breaking gently over a weakly submerged horizontal circular cylinder at a low Keulegan–Carpenter number. Each simulated case is supported by detailed comparisons with experimental data in time and frequency domain. The results presented have been obtained adopting a standard RANS approach. They show a generally good reproduction of the wave breaking characteristics even though it is rather clear that there is a case dependent potential loss of accuracy in the presence of pronounced foamy flow. Abstract : Highlights: We model numerically 2-D breaking waves in three cases. We compared the numerical results with laboratory data. We show that RANS approach can lead to inaccurate prediction of some wave features.